Method for improving binding force of thin film circuit and hexagonal single crystal ferrite
By depositing the base layer, the adhesion layer and the metal layer on the hexagonal single-crystal ferrite substrate and performing high temperature and high vacuum treatment, the problem of insufficient bonding force of the metal thin film circuit in the prior art is solved, and a high bonding film structure is realized, which improves the reliability of the device.
Patent Information
- Application Number
- CN202510054459.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively improve the bonding force of the metal thin film circuit on the surface of hexagonal single-crystal ferrite, resulting in insufficient device reliability.
Plasma etching treatment and magnetron sputtering technology are used to deposit the base layer, adhesion layer and metal layer on the hexagonal single-crystal ferrite substrate, and high temperature and high vacuum treatment are carried out before and after sputtering, the degree of substrate surface activation and the chemical bonding force of the film layer material is enhanced.
The bonding force between the metal thin film circuit and hexagonal single crystal ferrite is significantly improved, and the reliability of the device is enhanced, and the film bonding force can reach more than 1200g/mm2.
Smart Images

Figure CN119824379A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of microwave components, and in particular to a method for improving the bonding force between a thin film circuit and a hexagonal single crystal ferrite. Background Art
[0002] In recent years, with the rapid development of electronic technology, higher requirements have been put forward for microwave communication systems in terms of reliability, carrying power, and external dimensions. In order to meet these increasingly high performance requirements, microwave communication systems need to develop in the direction of high-density integration, which requires the components of communication transceivers to develop in the direction of miniaturization. In order to comply with the trend of miniaturization, the circulator, as the front-end device of the communication system, needs to be improved in terms of device size and other aspects.
[0003] Compared with gyromagnetic polycrystalline garnet and spinel ferrite, hexagonal single crystal ferrite has a very strong perpendicular anisotropy field. This magnetocrystalline anisotropy equivalent field is used to supplement the DC magnetic field generated by the permanent magnet, improve the normalized magnetic field of the ferrite bias, and make the high-field design of the high-frequency working circulator possible, further reduce the volume of the high-frequency circulator, and improve the power resistance of the circulator; based on the characteristics of the single crystal structure, its internal structure has good continuity and no grain boundary separation, and its corresponding magnetic loss and electrothermal loss are lower, which can further reduce the loss of the circulator; at the same time, due to the single crystal structure, the substrate surface is smooth, which is conducive to improving the manufacturing accuracy of thin film circuits and thin film resistors. Therefore, hexagonal single crystal ferrite can be used to prepare high-frequency circulators with smaller volume and lower loss. However, due to the good continuity of the outer surface structure of hexagonal single crystal ferrite and the stable physical and chemical properties, it is difficult to prepare a metal circuit with high bonding strength on its surface. If the bonding strength between the metal thin film circuit and the hexagonal single crystal ferrite is poor, the reliability of the device will be insufficient.
[0004] At present, the method to improve the bonding strength of metal thin film is generally to heat the substrate during magnetron sputtering of the metal film layer to improve the bonding strength between the metal thin film circuit and the substrate. However, according to the actual situation, it is found that heating during sputtering cannot completely and effectively improve the bonding strength of the metal thin film circuit on the substrate. The circuit film layer often falls off, which does not meet the bonding strength requirements of the circulator device application, affecting the reliability of the device.
[0005] Since the standard of the ring device does not define the size of the film layer bonding force, the aerospace military industry has a definition of the overall reliability of the device. Based on the above method, the metal film circuit on the hexagonal single crystal ferrite is made. The inventor uses the "bonding force pulling method" and the standard is ISO4624 for performance testing. It is found that with the current processing method, the film layer bonding force is generally only 100g / mm 2 about. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for improving the bonding strength between thin film circuits and hexagonal single crystal ferrite to solve the above-mentioned problem.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: a method for improving the bonding strength between a thin film circuit and a hexagonal single crystal ferrite, comprising the following steps: (1) Etching treatment: plasma etching equipment is used to perform plasma etching on the cleaned hexagonal single crystal ferrite substrate; (2) Pretreatment before sputtering: placing the hexagonal single crystal ferrite substrate treated in step (1) in a magnetron sputtering device, and achieving a high temperature and high vacuum state in the cavity by increasing the vacuum degree and cavity temperature; (3) Material deposition: After pretreatment, a radio frequency power source is used to deposit the base layer, adhesion layer, and metal layer on the substrate surface; (4) Post-sputtering treatment: Maintain high temperature and high vacuum in the sputtering chamber until the treatment is completed; The present invention firstly greatly improves the activation degree of the substrate surface through special pre-sputtering pretreatment, so that the deposited film material has better chemical bonding force; Then, by depositing a primer layer and an adhesion layer on the hexagonal single crystal ferrite, the bonding force between the film material and the hexagonal single crystal ferrite is greatly improved, and the reliability of the metal film layer is enhanced; Finally, through special sputtering post-treatment, the mutual diffusion degree between the film material and the substrate can be effectively enhanced, so that the bonding force is further enhanced.
[0008] As a preferred technical solution, in step (1), the plasma etching method is: using Ar plasma etching, with an Ar gas flow rate of 20 to 50 sccm and a power of 100 to 400 W.
[0009] As a preferred technical solution, in step (2), the pre-sputtering pretreatment method is: vacuum degree ≤ 3×10 - 4 Pa, the cavity temperature is 200-600℃, the heating rate is 5-40℃ / min, and the holding time is 0.5-5h.
[0010] As a preferred technical solution, in step (3), the base material is selected from SiO2, TiN, Cr, Ti x W 1-x 、Co y W 1-yOne or more of the following, wherein x≤0.5, y≤0.5; the thickness of the base layer is 50-300 nm, the sputtering temperature is 200-600° C., the sputtering power is 150W-400W, and the sputtering pressure is 0.2-5Pa.
[0011] As a preferred technical solution, in step (3), the adhesion layer material is selected from TaN, Cr, Ti, Ti x W 1-x 、Co y W 1-y One or more of the following, wherein x≤0.5, y≤0.5. The thickness of the adhesion layer is 50-300 nm, the sputtering temperature is 200-600° C., the sputtering power is 150W-400W, and the sputtering pressure is 0.2-5Pa.
[0012] As a preferred technical solution, in step (3), the metal layer material is selected from one or more of Cu, Ni, Ti, Au, and Al; the metal layer thickness is 200nm to 4000nm, the sputtering temperature is 200 to 600°C, the sputtering power is 200W to 500W, and the sputtering gas pressure is 0.2 to 5Pa.
[0013] As a preferred technical solution, in step (4), the post-sputtering treatment method is: vacuum degree ≤ 3×10 -4 Pa, the cavity temperature is 200-600℃, the heating rate is 5-20℃ / min, and the holding time is 2-5h.
[0014] The second object of the present invention is to provide a high-binding strength film layer structure prepared by the above method, which comprises, from bottom to top: a hexagonal single crystal ferrite material layer, a primer layer, an adhesion layer and a metal layer.
[0015] Compared with the prior art, the advantages of the present invention are: the base layer and adhesion layer deposited on the hexagonal single crystal ferrite of the present invention greatly improve the bonding force between the film material and the hexagonal single crystal ferrite, and enhance the reliability of the metal film layer; combined with the substrate processing method provided by the present invention, the activation degree of the substrate surface is greatly improved, so that the deposited film material has better chemical bonding force, and the processing method after the film material of the present invention is prepared can effectively enhance the degree of mutual diffusion between the film material and the substrate, so that the bonding force is further enhanced; the present invention provides a variety of film materials for selection, and has very strong adjustability for different application scenarios and process conditions, and the process method is simple and effective. For example, when using hexagonal single crystal ferrite material as a substrate for surface metal circuit production, SiO2 can be used as a base layer and TiW as an adhesion layer, and metal film layers such as Cu and Au are prepared thereon. SiO2 and TiW can be respectively bonded with the lower hexagonal single crystal ferrite material and the upper Cu and Au metals with high strength, and the film bonding force can reach 1200g / mm 2 For example, when hexagonal single crystal ferrite and alumina ceramic are heterogeneously combined to form a composite substrate, the bonding strength between SiO2 material and alumina ceramic is poor, so it is not suitable for this type of composite substrate. Another TiW base material and TiN provided by the present invention can be used as adhesion layer materials. TiW and TiN can be highly bonded to the hexagonal single crystal ferrite material and alumina ceramic material, respectively. TiN can be highly bonded to the upper layer of Cu and Au metals, and the film bonding strength can reach 700g / mm 2 The above meets the device usage requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a film structure diagram of Example 1 of the present invention; Figure 2 Schematic cross-sectional view of the hexagonal single crystal ferrite and alumina ceramic composite substrate of Example 3 of the present invention.
[0017] In the figure: 1, hexagonal single crystal ferrite material layer; 2, primer layer; 3, adhesion layer; 4, metal layer; 5, hexagonal single crystal ferrite material layer; 6, welding seam; 7, alumina ceramic; DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with the accompanying drawings.
[0019] It should be noted that the following embodiments all adopt the "bonding force pulling method" and the standard ISO4624 to perform the performance test of the bonding force of the film layer.
[0020] Embodiment 1:
[0021] A high-binding membrane structure, the structure of which is as follows Figure 1As shown, it includes, from bottom to top, a hexagonal single crystal ferrite substrate 1, a base layer 2, an adhesion layer 3 and a metal layer 4, and its preparation method includes the following steps: (1) subjecting the hexagonal single crystal ferrite substrate to a standard wet cleaning process known in the art to remove contaminants on the surface of the material; (2) Place the cleaned hexagonal single crystal ferrite material substrate in a dry etching device and perform dry etching on the substrate surface: use a radio frequency power supply, introduce Ar gas for ignition, the Ar gas flow rate is set to 25 sccm, and the radio frequency power supply power is 300 W; after successful ignition, open the ion source baffle and keep it for 300 seconds, then terminate the program and take the wafer; (3) Place the hexagonal single crystal ferrite substrate in the magnetron sputtering equipment and start vacuuming; when the vacuum degree is less than 3*10 -4 After Pa, the temperature in the equipment cavity begins to rise, with a heating rate of 15°C / min and a target temperature of 500°C. After reaching the target temperature, this state is maintained for 2 hours; (4) After the above steps are completed, the film sputtering is started: SiO2 is used as the base layer 2, the sputtering temperature is 500°C, the Ar gas flow rate is 20sccm, the sputtering power is 200W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 80nm; TiW is used as the adhesion layer 3, the sputtering temperature is 500°C, the Ar gas flow rate is 20sccm, the sputtering power is 250W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 50nm; Cu is used as the metal layer 4, the sputtering temperature is 400°C, the Ar gas flow rate is 25sccm, the sputtering power is 500W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 3500nm; (5) After sputtering is completed, the chamber temperature of the magnetron sputtering equipment is increased to 600°C at a heating rate of 5°C / min. After reaching the target temperature, this state is maintained for 2 hours. After completion, the program is closed and the chamber temperature is opened for sampling when it naturally cools down to below 100°C. Through the above method, we can obtain Figure 1 The film structure shown in the figure is tested. The film bonding strength of the metal thin film circuit on the hexagonal single crystal ferrite made based on the above method is 1200g / mm 2 .
[0022] Embodiment 2: A high-binding membrane structure, the structure of which is as follows Figure 2 As shown, from the inside to the outside, it includes hexagonal single crystal ferrite 5, welding seam 6, and alumina ceramic 7, and its preparation method includes the following steps:
[0023] A high-bonding film layer structure, the structure of which is the same as that of Example 1, comprises, from bottom to top, a hexagonal single crystal ferrite substrate 1, a primer layer 2, an adhesion layer 3 and a metal layer 4, and the preparation method thereof comprises the following steps: (1) subjecting the hexagonal single crystal ferrite substrate to a standard wet cleaning process known in the art to remove contaminants on the surface of the material; (2) Place the cleaned hexagonal single crystal ferrite substrate in a dry etching device and perform dry etching on the substrate surface: use a radio frequency power supply, introduce Ar gas for ignition, the Ar gas flow rate is set to 20 sccm, and the radio frequency power supply power is 400 W; after ignition is successful, open the ion source baffle and keep it for 300 seconds, then terminate the program and take the substrate; (3) Place the hexagonal single crystal ferrite substrate in the magnetron sputtering equipment and start vacuuming; when the vacuum degree is less than 3*10 -4 After Pa, the temperature in the equipment cavity begins to rise, with a heating rate of 15°C / min and a target temperature of 200°C. After reaching the target temperature, this state is maintained for 5 hours; (4) After the above steps are completed, the film sputtering is started: SiO2 is used as the base layer 2, the sputtering temperature is 200°C, the Ar gas flow rate is 50sccm, the sputtering power is 400W, the sputtering pressure is 3Pa, and the sputtering thickness is 300nm; TiW is used as the adhesion layer 3, the sputtering temperature is 200°C, the Ar gas flow rate is 50sccm, the sputtering power is 400W, the sputtering pressure is 3Pa, and the sputtering thickness is 150nm; Cu is used as the metal layer 4, the sputtering temperature is 200°C, the Ar gas flow rate is 50sccm, the sputtering power is 200W, the sputtering pressure is 3Pa, and the sputtering thickness is 3500nm; (5) After the sputtering is completed, the chamber temperature of the magnetron sputtering equipment is maintained at 200°C for 5 hours; after completion, the program is closed and the chamber temperature is opened for sampling when it naturally cools down to below 100°C; Through the above method, we can obtain Figure 1 The film structure shown in the figure is tested. The film bonding strength of the metal thin film circuit on the hexagonal single crystal ferrite made based on the above method is 900g / mm 2 .
[0024] Example 2 is based on the above-mentioned Example 1, and some process parameters are changed. The process parameters and the film layer bonding strength of the metal thin film circuit on the hexagonal single crystal ferrite are shown in Table 1 below: Table 1 Comparison of process parameters of Examples 1 and 2
[0025] Embodiment 3:
[0026] A high-binding membrane structure, the structure of which is as follows Figure 2 As shown, from the inside to the outside, it includes hexagonal single crystal ferrite 5, welding seam 6, and alumina ceramic 7, and its preparation method includes the following steps:
[0027] (1) subjecting the hexagonal single crystal ferrite and alumina ceramic composite substrate to a standard wet cleaning process known in the art to remove contaminants on the surface of the material; (2) Place the cleaned hexagonal single crystal ferrite and alumina ceramic composite substrate in a dry etching device and perform dry etching on the substrate surface: use a radio frequency power supply, introduce Ar gas for ignition, the Ar gas flow rate is set to 20 sccm, and the radio frequency power supply power is 400 W; after successful ignition, open the ion source baffle and keep it for 300 seconds, then terminate the program and take the wafer; (3) Place the hexagonal single crystal ferrite and alumina ceramic composite substrate in a magnetron sputtering device and start vacuuming; when the vacuum degree is less than 3*10 -4 After Pa, the temperature in the equipment cavity begins to rise, with a heating rate of 15°C / min and a target temperature of 500°C. After reaching the target temperature, this state is maintained for 3 hours; (4) After the above steps are completed, the film sputtering is started: TiW is used as the base layer 2, the sputtering temperature is 300°C, the Ar gas flow rate is 25sccm, the sputtering power is 250W, the sputtering pressure is 0.5Pa, and the sputtering thickness is 150nm; TiN is used as the adhesion layer 3, the sputtering temperature is 250°C, the Ar gas flow rate is 25sccm, the sputtering power is 300W, the sputtering pressure is 0.5Pa, and the sputtering thickness is 120nm; Cu is used as the metal layer 4, the sputtering temperature is 200°C, the Ar gas flow rate is 50sccm, the sputtering power is 200W, the sputtering pressure is 0.5Pa, and the sputtering thickness is 3500nm; (5) After sputtering is completed, the chamber temperature of the magnetron sputtering equipment is increased to 600°C at a heating rate of 5°C / min. After reaching the target temperature, this state is maintained for 2 hours. After completion, the program is closed and the chamber temperature is opened for sampling when it naturally cools down to below 100°C. Through the above method, we can obtain Figure 1 The film structure shown in the figure is tested. The film bonding strength of the metal thin film circuit on the hexagonal single crystal ferrite made based on the above method is 700g / mm 2 .
[0028] Comparative Example 1: The sputtering temperature of step (3) of the above embodiment is changed to 100° C. The specific production steps are as follows: (1) subjecting the hexagonal single crystal ferrite substrate to a standard wet cleaning process known in the art to remove contaminants on the surface of the material; (2) Place the cleaned hexagonal single crystal ferrite material substrate in a dry etching device and perform dry etching on the substrate surface: use a radio frequency power supply, introduce Ar gas for ignition, the Ar gas flow rate is set to 25 sccm, and the radio frequency power supply power is 300 W; after successful ignition, open the ion source baffle and keep it for 300 seconds, then terminate the program and take the wafer; (3) Place the hexagonal single crystal ferrite substrate in the magnetron sputtering equipment and start vacuuming; when the vacuum degree is less than 3*10 -4 After Pa, the temperature in the equipment cavity begins to rise, with a heating rate of 15°C / min and a target temperature of 100°C. After reaching the target temperature, this state is maintained for 2 hours; (4) After the above steps are completed, the film sputtering is started: SiO2 is used as the base layer 2, the sputtering temperature is 100°C, the Ar gas flow rate is 20sccm, the sputtering power is 200W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 80nm; TiW is used as the adhesion layer 3, the sputtering temperature is 100°C, the Ar gas flow rate is 20sccm, the sputtering power is 250W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 50nm; Cu is used as the metal layer 4, the sputtering temperature is 400°C, the Ar gas flow rate is 25sccm, the sputtering power is 500W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 3500nm; (5) After sputtering is completed, the chamber temperature of the magnetron sputtering equipment is increased to 600°C at a heating rate of 5°C / min. After reaching the target temperature, this state is maintained for 2 hours. After completion, the program is closed and the chamber temperature is opened for sampling when it naturally cools down to below 100°C. The film structure obtained by the above method was tested and the film bonding strength of the metal thin film circuit on the hexagonal single crystal ferrite made by the above method was 180g / mm 2 , the condition of this comparative example is to reduce the sputtering temperature to 100°C. During the sputtering process of the thin film, the incident particles bombard the target material with high energy. After obtaining sufficient energy, the atoms on the surface of the target material will carry part of the energy to overflow from the surface and adsorb on the substrate. Since the substrate is heated during the sputtering process, the atoms adsorbed to the substrate will obtain additional energy in addition to the energy they carry. As the sputtering temperature changes, the deposition of atoms on the surface of the substrate will also change. The material grains grow on the substrate as a substrate. The higher the temperature, the higher the activation degree of the surface properties of the substrate, and the deeper the mutual diffusion depth between the atoms in the grains and the shallow surface layer of the substrate, that is, the stronger the bonding force between the two.
[0029] Comparative Example 2: Eliminate the above step (2), that is, the dry etching pretreatment process, and the specific production steps are as follows: (1) subjecting the hexagonal single crystal ferrite substrate to a standard wet cleaning process known in the art to remove contaminants on the surface of the material; (2) Place the hexagonal single crystal ferrite substrate in the magnetron sputtering equipment and start vacuuming; when the vacuum degree is less than 3*10 -4 After Pa, the temperature in the equipment cavity begins to rise, with a heating rate of 15°C / min and a target temperature of 500°C. After reaching the target temperature, this state is maintained for 2 hours; (3) After the above steps are completed, the film sputtering is started: SiO2 is used as the base layer 2, the sputtering temperature is 500°C, the Ar gas flow rate is 20sccm, the sputtering power is 200W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 80nm; TiW is used as the adhesion layer 3, the sputtering temperature is 500°C, the Ar gas flow rate is 20sccm, the sputtering power is 250W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 50nm; Cu is used as the metal layer 4, the sputtering temperature is 400°C, the Ar gas flow rate is 25sccm, the sputtering power is 500W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 3500nm; (4) After the sputtering is completed, the chamber temperature of the magnetron sputtering equipment is increased to 600°C at a heating rate of 5°C / min. After reaching the target temperature, this state is maintained for 2 hours. After completion, the program is closed and the chamber temperature is opened for sampling when it naturally cools down to below 100°C. The film structure obtained by the above method was tested and the film bonding strength of the metal thin film circuit on the hexagonal single crystal ferrite made by the above method was 100g / mm 2 The dry etching process uses high-energy Ar plasma to bombard the substrate surface. Under the action of high-energy particles, the surface activation and roughness of the substrate are improved, so that the atomic diffusion and physical riveting between the substrate surface and the film are improved.
[0030] Comparative Example 3: Eliminate the above step (5), i.e. the post-sputtering processing flow, and the specific production steps are as follows: (1) subjecting the hexagonal single crystal ferrite substrate to a standard wet cleaning process known in the art to remove contaminants on the surface of the material; (2) Place the cleaned hexagonal single crystal ferrite material substrate in a dry etching device and perform dry etching on the substrate surface: use a radio frequency power supply, introduce Ar gas for ignition, the Ar gas flow rate is set to 25 sccm, and the radio frequency power supply power is 300 W; after successful ignition, open the ion source baffle and keep it for 300 seconds, then terminate the program and take the wafer; (3) Place the hexagonal single crystal ferrite substrate in the magnetron sputtering equipment and start vacuuming; when the vacuum degree is less than 3*10 -4 After Pa, the temperature in the equipment cavity begins to rise, with a heating rate of 15°C / min and a target temperature of 500°C. After reaching the target temperature, this state is maintained for 2 hours; (4) After the above steps are completed, the film sputtering is started: SiO2 is used as the base layer 2, the sputtering temperature is 500°C, the Ar gas flow rate is 20sccm, the sputtering power is 200W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 80nm; TiW is used as the adhesion layer 3, the sputtering temperature is 500°C, the Ar gas flow rate is 20sccm, the sputtering power is 250W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 50nm; Cu is used as the metal layer 4, the sputtering temperature is 400°C, the Ar gas flow rate is 25sccm, the sputtering power is 500W, the sputtering pressure is 0.8Pa, and the sputtering thickness is 3500nm; (5) After the sputtering is completed, the program is closed and the cavity is opened for sampling when the cavity temperature naturally cools down to below 100°C; The film structure obtained by the above method was tested and the film bonding strength of the metal thin film circuit on the hexagonal single crystal ferrite made by the above method was 210g / mm 2 After the sputtering is completed, the substrate and the thin film material are kept in a vacuum and high temperature environment for a period of time to further enhance the mutual diffusion and bonding strength between the substrate and the thin film material.
[0031] Comparative Example 4: Cancel the base material, the specific production steps are as follows: (1) subjecting the hexagonal single crystal ferrite substrate to a standard wet cleaning process known in the art to remove contaminants on the surface of the material; (2) Place the cleaned hexagonal single crystal ferrite material substrate in a dry etching device and perform dry etching on the substrate surface: use a radio frequency power supply, introduce Ar gas for ignition, the Ar gas flow rate is set to 25 sccm, and the radio frequency power supply power is 300 W; after successful ignition, open the ion source baffle and keep it for 300 seconds, then terminate the program and take the wafer; (3) Place the hexagonal single crystal ferrite substrate in the magnetron sputtering equipment and start vacuuming; when the vacuum degree is less than 3*10 -4 After Pa, the temperature in the equipment cavity begins to rise, with a heating rate of 15°C / min and a target temperature of 400°C. After reaching the target temperature, this state is maintained for 2 hours; (4) After the above steps are completed, the film sputtering is started: TiW is used as the adhesion layer 3, the sputtering temperature is 400°C, the Ar gas flow rate is 20 sccm, the sputtering power is 250 W, the sputtering pressure is 0.8 Pa, and the sputtering thickness is 50 nm; Cu is used as the metal layer 4, the sputtering temperature is 400°C, the Ar gas flow rate is 25 sccm, the sputtering power is 500 W, the sputtering pressure is 0.8 Pa, and the sputtering thickness is 3500 nm; (5) After sputtering is completed, the chamber temperature of the magnetron sputtering equipment is increased to 600°C at a heating rate of 5°C / min. After reaching the target temperature, this state is maintained for 2 hours. After completion, the program is closed and the chamber temperature is opened for sampling when it naturally cools down to below 100°C. The film structure obtained by the above method was tested and the film bonding strength of the metal thin film circuit on the hexagonal single crystal ferrite made by the above method was 700g / mm 2 As mentioned above, the present invention provides a variety of film material options, which are highly adjustable for different application scenarios and process conditions, and the process is simple and effective, including the use of SiO2 as the base layer and TiW as the adhesion layer, and the film bonding strength reaches 1200g / mm 2 The above; using TiW as the base material and TiN as the adhesion layer material, the film bonding strength can reach 700g / mm 2 Both film structures contain TiW, which is used as the base layer and adhesion layer material respectively. When other process conditions are optimized, the bonding strength of the two can reach 1200g / mm 2 Above and 700g / mm 2 As shown above, TiW has a strong bonding force with both the upper metal layer and the lower hexagonal single crystal ferrite material. In this comparative example, only TiW is used as the lower film material, which is equivalent to using TiW as both the base layer and the adhesion layer. When other process conditions are met, the bonding force can reach 700g / mm 2 This comparative example not only illustrates that dry etching pretreatment is more important than the setting of the base layer, but also illustrates that the bonding strength of the film layer will be affected by the difference in the base layer material.
[0032] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the bonding strength between a thin film circuit and hexagonal single crystal ferrite, characterized in that: The steps include: (1) Etching treatment: plasma etching equipment is used to perform plasma etching on the cleaned hexagonal single crystal ferrite substrate; (2) Pre-sputtering pretreatment: placing the hexagonal single crystal ferrite substrate treated in step (1) in a magnetron sputtering device, and achieving a high temperature and high vacuum state in the cavity by increasing the vacuum degree and cavity temperature; (3) Material deposition: After pretreatment, a radio frequency power source is used to deposit the base layer, adhesion layer, and metal layer on the substrate surface; (4) Post-sputtering treatment: In the sputtering chamber, maintain high temperature and high vacuum conditions until the treatment is completed.
2. The method according to claim 1, characterized in that In step (1), the plasma etching treatment method is: using Ar plasma etching, the Ar gas flow rate is 20-50 sccm, and the power is 100-400W.
3. The method according to claim 1, characterized in that In step (2), the pre-sputtering pretreatment method is: vacuum degree ≤ 3×10 -4 Pa, the cavity temperature is 200-600℃, the heating rate is 5-40℃ / min, and the holding time is 0.5-5h.
4. The method according to claim 1, characterized in that In step (3), the base material is selected from SiO2, TiN, Cr, Ti x W 1-x 、Co y W 1-y One or more of the following, wherein x≤0.5, y≤0.5; the thickness of the base layer is 50-300 nm, the sputtering temperature is 200-600° C., the sputtering power is 150W-400W, and the sputtering pressure is 0.2-5Pa.
5. The method according to claim 1, characterized in that In step (3), the adhesion layer material is selected from TaN, Cr, Ti, Ti x W 1-x 、Co y W 1-y One or more of the following, wherein x≤0.5, y≤0.
5. The thickness of the adhesion layer is 50-300 nm, the sputtering temperature is 200-600° C., the sputtering power is 150W-400W, and the sputtering pressure is 0.2-5Pa.
6. The method according to claim 1, characterized in that In step (3), the metal layer material is selected from one or more of Cu, Ni, Ti, Au, and Al; the thickness of the metal layer is 200 nm to 4000 nm, the sputtering temperature is 200 to 600° C., the sputtering power is 200 W to 500 W, and the sputtering pressure is 0.2 to 5 Pa.
7. The method according to claim 1, characterized in that In step (4), the post-sputtering treatment method is: vacuum degree ≤ 3×10 -4 Pa, the cavity temperature is 200-600℃, the heating rate is 5-20℃ / min, and the holding time is 2-5h.
8. A high-binding film structure obtained by the method of any one of claims 1 to 7, characterized in that: From bottom to top, they are: a hexagonal single crystal ferrite material layer (1), a base layer (2), an adhesion layer (3) and a metal layer (4).